PENERAPAN DATA MINING UNTUK PERAMALAN TARGET PRODUKSI MINUMAN JUS KEMASAN MENGGUNAKAN METODE LINEAR REGRESI BERGANDA - Nugraha, Diat Ridwan; Tumini, Tumini (Jurnal informasi dan komputer, 2023)
This study aims to apply one of the data mining techniques by applying the linear regression method in the beverage production planning process. Data mining is a data analysis technique used to identify patterns, relationships, and valuable information from large data sets. The linear regression method is one of the statistical methods used to model the relationship between the independent variables and the dependent variable. In this study, the data collected includes variables related to beverage production, such as sales results, the number of orders and the amount of production. The linear regression method will be used to build a mathematical model that can predict the amount of beverage production based on the existing variables. The results of this study are expected to provide valuable insights into the beverage production planning process. Using the linear regression method can assist companies in forecasting future beverage production based on patterns and trends found from data analysis. This can help companies manage raw material inventories, optimize resource use, and reduce production costs. The results of this study can be used as a basis for making better and more efficient decisions in managing beverage production, as well as providing significant economic benefits for the company.